A Digital Platform and Smartphone App to Increase Physical Activity in Patients With Type 2 Diabetes: Overview Of a Technical Solution - Stephanie E Bonn; Christina Alexandrou; Ylva Trolle Lagerros (JMIR Formative Research, 2023)
International Registered Report Identifier (IRRID) RR2-10.1186/s12889-018-5026-4